Revisiting task orientated care: Oral histories of former student nurses in Ireland (1960–2001). (March 2018) - Fallon, Anne; Chiardha, Toni Uí; Meaney, Teresa; van der Putten, Deirdre; Brennan, Miriam; Chionna, Jackie Uí; Bradley, Stephen; McNicholas, Miriam; Smyth, Siobhan
Abstract: The apprenticeship model of nurse training was in place in Ireland up to the end of the twentieth century. Task orientated care was a feature of this model. It is important to examine task allocation from the student's perspective, in light of current and on-going debates regarding student nurses' supernumerary status. Both approaches influence the status of the student; as a worker with task allocation and as a learner with supernumerary status. Oral history interviews were undertaken with twelve former student nurses (1960–2001) to explore their experiences of clinical learning and task allocation. Task allocation consisted of household tasks and tasks involving patient care. Students' experiences were influenced more by issues surrounding the task, particularly the 'task-person', than the task itself. Therefore, a learning environment that is inclusive, supportive and understanding of students' learning is recommended, regardless of the model of nurse training or education that might be in place. These findings can inform current debate on supernumerary status and task allocation for the student nurse within their clinical learning environment, but also on the history of nurse education in Ireland in the twentieth century. Highlights: Tasks consisted of household tasks and tasks involving patient care. Student nurses learned the task by observing and imitating others. Student nurses were aware the task had to be completed quickly and correctly. Student nurses had coping strategies to deal with stresses surrounding the task. The task-person influenced student nurses' experiences more than the task itself.